Prioritizing work for family: A Chinese indigenous perspective. Issue 1 (6th May 2014) - Zhang, Mian; Li, Hai; Foley, Sharon
Abstract : Purpose: – The purpose of this paper was to develop an indigenous understanding of work-family interface (WFI) that reflects the drastic changes and evolving social context in China over the past three decades and challenge the existing conceptualizations of WFI and identify societal impact of the changing nature of the WFI. Design/methodology/approach: – We conducted literature review, content and thematic analyses. Findings: – The core idea of prioritizing work for family (PWF) is that Chinese employees, especially Chinese male employees, tend to integrate work and family roles as well as deal with WFI issues at the family level. Thus, Chinese employees can be strongly committed to the family while simultaneously prioritizing work performance. Research limitations/implications: – The proposed indigenous perspective of PWF may furnish a contextualized theory for future research. The proposed measurement approaches may help developing indigenous scales for the perspective of PWF for future empirical studies. Practical implications: – Although Chinese employees tend to be more tolerant of work-family conflict (WFC) than their Western counterparts, such tolerance may be combined with the expectation of long-term returns to their families. Managers may assist employees with career planning and realistic goal setting to compensate for their endurance of WFC. Social implications: – As a cornerstone of the society, the family plays an important role in building a "harmonious society" promoted by the government. A perceived balance of work and family is a significant factor for family harmony. We bring to the attention of policy makers the changing nature of the Chinese employees' WFI. A corresponding policy may be formulated to help Chinese employees balance their lives. Originality/value: – We challenge the existing conceptualizations of WFI by proposing and elaborating a perspective of PWF for context-based conceptualization.